Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.11606/issn.2318-3659.v49i5p345-353
|View full text |Cite
|
Sign up to set email alerts
|

Aerocistite aguda induzida por tioglicolato, lipolisacarídeo e Aeromona hydrophila inativada em Piaractus mesopotamicus: efeitos hematológicos

Abstract: The effects of swim bladder injection with thioglycolate, Escherichia coli lipopolysaccharide (LPS) and heat-inactivated Aeromonas hydrophila were assessed on hematological responses in pacu, Piaractus mesopotamicus (Characidae). A quantitative assessment was done on erythrocytes, thrombocytes e leucocytes at 6, 24, and 48 h pos-injection of the inflammatory agents and compared with fish injected with saline solution (control). Fish injected with inactivated A. hydrophila showed a reduction of erythrocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The presence of eosinophils and basophils in fish from 1% and 4% group could be considered positive, since, in the face of any pathogenic agents, these fish could trigger a quick and effective defence response of the organism. PAS‐positive granular leucocytes (PAS‐GL), formerly called special granulocytic cells (SGC), are little remembered in haematological studies of fish (Tavares‐Dias et al, 1999); however, they are blood cells commonly observed in inflammatory foci (Moraes et al, 2012). Mohamed and Refat (2011) observed that the probiotic B .…”
Section: Probiotic Inclusion Levels Haematological Parameter mentioning
confidence: 99%
“…The presence of eosinophils and basophils in fish from 1% and 4% group could be considered positive, since, in the face of any pathogenic agents, these fish could trigger a quick and effective defence response of the organism. PAS‐positive granular leucocytes (PAS‐GL), formerly called special granulocytic cells (SGC), are little remembered in haematological studies of fish (Tavares‐Dias et al, 1999); however, they are blood cells commonly observed in inflammatory foci (Moraes et al, 2012). Mohamed and Refat (2011) observed that the probiotic B .…”
Section: Probiotic Inclusion Levels Haematological Parameter mentioning
confidence: 99%
“…Farmed fish are in constant contact with different agents capable of provoking inflammatory condition (MARTINS et al, 2001) Inflammatory response has been evaluated under several factors such as fish fed supplemented diets containing vitamins (BELO et al, 2005;MARTINS et al, 2008a;BELO et al, 2012), probiotics (REQUE et al, 2010;DOTTA et al, 2011;CASTRO et al, 2014a), amino acids, minerals and polysaccharides (FALCO et al, 2012;CASTRO et al, 2014b;MACHADO et al, 2015), phytotherapics (DOTTA et al, 2015), stocking density (BELO et al, 2005) and the stressful effect on inflammatory response (MARTINS et al, 2004). Some phlogogen agents have been used to stimulate cell migration and the most used are carrageenin (MATUSHIMA; MARIANO, 1996;MARTINS et al, 2001;MARTINS et al, 2004;MARTINS et al, 2008a;MARTINS et al, 2009;DOTTA et al, 2011), thioglycolate (MARTINS et al, 2001;BOZZO et al, 2007;MARTINS et al, 2009;MORAES et al, 2012), lipopolysaccharides (LPS) (MARTINS et al, 2004;BOZZO et al, 2007;MARTINS et al, 2008a;MORAES et al, 2012), inactivated bacteria (BOZZO et al, 2007;REQUE et al, 2010;MORAES et al, 2012;CLAUDIANO et al, 2013;CASTRO et al, 2014b;MACHADO et al, 2015) and glass coverslip (BELO et al, 2005;BELO et al, 2012). In Brazil, the inflammatory process in fish was studied in pacu Piaractus mesopotamicus …”
Section: Introductionmentioning
confidence: 99%
“…Some phlogogen agents have been used to stimulate cell migration and the most used are carrageenin (MATUSHIMA; MARIANO, 1996;MARTINS et al, 2001;MARTINS et al, 2004;MARTINS et al, 2008a;MARTINS et al, 2009;DOTTA et al, 2011), thioglycolate (MARTINS et al, 2001;BOZZO et al, 2007;MARTINS et al, 2009;MORAES et al, 2012), lipopolysaccharides (LPS) (MARTINS et al, 2004;BOZZO et al, 2007;MARTINS et al, 2008a;MORAES et al, 2012), inactivated bacteria (BOZZO et al, 2007;REQUE et al, 2010;MORAES et al, 2012;CLAUDIANO et al, 2013;CASTRO et al, 2014b;MACHADO et al, 2015) and glass coverslip (BELO et al, 2005;BELO et al, 2012). In Brazil, the inflammatory process in fish was studied in pacu Piaractus mesopotamicus (BELO et al, 2005;BOZZO et al, 2007;GARCIA et al, 2007;MORAES, 2009;BELO et al, 2012;CLAUDIANO et al, 2013;MORAES et al, 2012;CASTRO et al, 2014b), Nile tilapia Oreochromis niloticus (MATUSHIMA; MARIANO, 1996;MARTINS et al, 2004;MARTINS et al, 2008a;REQUE et al, 2010;DOTTA et al, 2011) and in the hybrid tambacu (P. mesopotamicus male x Colossoma macropomum female) (MARTINS et al, 2001;MARTINS et al, 2009).…”
Section: Introductionmentioning
confidence: 99%